2018
DOI: 10.1016/j.jiph.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards Zika virus among medical students in King Abdulaziz University, Jeddah, Saudi Arabia

Abstract: Zika Virus (ZIKV) and its associated consequences remain vital public health challenge of international concerns. The current study was done to assess knowledge and attitudes towards ZIKV and the factors associated with good knowledge among medical students in King Abdulaziz University, Jeddah. A cross-sectional study was conducted among 426 students. They were selected through multistage stratified random sample method, 2016. A validated, confidential, interviewing questionnaire contained 25 knowledge and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 30 publications
(41 reference statements)
9
36
0
Order By: Relevance
“…Respondents in this study also exhibited better knowledge on this, than what was found in Greece in 2016 (36.7%) [28]. A more worrisome finding on this (17.1%) was recorded in Saudi Arabia among medical students in 2017 [34]. One would have expected medical students to be more knowledgeable on Zika virus than the general public.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Respondents in this study also exhibited better knowledge on this, than what was found in Greece in 2016 (36.7%) [28]. A more worrisome finding on this (17.1%) was recorded in Saudi Arabia among medical students in 2017 [34]. One would have expected medical students to be more knowledgeable on Zika virus than the general public.…”
Section: Discussionsupporting
confidence: 43%
“…. Surprisingly, this score is better than scores recorded in similar studies in some more developed countries such as Qatar (22.9%), and Saudi Arabia (30.3%) [27] [34]. It is important that women, and the general public are equipped with the knowledge that Zika virus can be transmitted through blood transfusion, so that they request for Zika virus blood screening before transfusion, in times of outbreak.…”
Section: Discussionmentioning
confidence: 61%
“…Studies related to knowledge and attitude towards ZIKV infection have been conducted in various community groups. At least 21 studies related to knowledge of ZIKV infection have been conducted [1,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52], in the general population [33][34][35][36][37] or specific groups such as reproductive-age women [38,39], pregnant women [40][41][42][43], construction workers [44], and medical [1,39,[45][46][47][48][49]52] and non-medical university students [33,52]. Five of these studies were conducted among HCWs [1,39,45,50,51].…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, one report addressed the knowledge of the surveyed HCP [14], whilst another has recently addressed the attitude of medical doctors [15]. In the Middle East, nurses' knowledge regarding ZIKAV screening in pregnant women was assessed in a study in Bahrain [16], while in Saudi Arabia, ZIKAV knowledge and attitude were assessed in a sample of medical students [17]. To the best of our knowledge, this is the first systematic report that addressed this issue specifically amongst general physicians and gynecologists, the two categories of physicians who are most probably encountering pregnant women that require counseling concerning ZIKAV.…”
Section: Introductionmentioning
confidence: 99%